A perfect storm of intervention? Lesbian and cisgender queer women conceiving through Australian fertility clinics. Issue 2 (15th March 2022) - Dempsey, Deborah; Power, Jennifer; Kelly, Fiona
ABSTRACT: Amendments to various state laws have made it easier for cisgendered lesbian, bisexual and queer (LBQ) women to access Australian fertility clinics. When women conceive through clinics, they generally use intrauterine insemination (IUI) or in vitro fertilisation (IVF). IUI is cheaper and requires less invasive medical intervention than IVF. A recent survey found that almost 60% of Australian cisgendered LBQ women who conceived with clinical assistance did so using IVF, despite most presenting to clinics without a diagnosis of infertility and seeking donor sperm only. In this paper, based on 20 interviews with Australian clinicians who treat LBQ patients seeking pregnancy, we explore potential explanations for why over half of LBQ women using Australian fertility clinics to conceive used IVF rather than IUI. A 'perfect storm' of factors appears to converge in this tendency. Although some LBQ women are purposefully choosing IVF to achieve biological relatedness for two mothers, other pressures toward high intervention conceptions include the distinction between 'social' and 'clinical' infertility by Medicare (the Australian national health insurance scheme), the relative profitability of IVF procedures and issues with the supply and quality of donor sperm. Accessing sperm from clinics appears to set some Australian women without male partners on a potentially unnecessary path to a high intervention and costly conception.